1959
DOI: 10.1111/j.1476-5381.1959.tb00943.x
|View full text |Cite
|
Sign up to set email alerts
|

The Central Vasomotor Effects of 5‐hydroxytryptamine

Abstract: In the dog, injection of 5-hydroxytryptamine into the cerebral ventricles caused hypotension, inhibition of the pressor response to occlusion of the carotid artery and inhibition of the pressor or depressor response evoked by electrical stimulation of the central end of the cut vagus. Hypotension and inhibition of the vagal vasomotor response also occurred in dogs in which the carotid sinuses had been denervated and the vagi cut. The site of action was central. Local cerebral vascular changes could not have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

1963
1963
1995
1995

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 8 publications
(4 reference statements)
1
23
0
Order By: Relevance
“…Two or three hours after the surgical procedure, when the urine flow rate was constant over a period of 30 min, the drugs were administered through a cannula implanted in one of the lateral cerebral ventricles (Bhargava & Tangri, 1959 (Innes & Nickerson, 1970). In a previous study, intracerebroventricular injection of histamine was shown to induce an antidiuretic response which has been attributed to a massive release of catecholamines (Bhargava et al, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…Two or three hours after the surgical procedure, when the urine flow rate was constant over a period of 30 min, the drugs were administered through a cannula implanted in one of the lateral cerebral ventricles (Bhargava & Tangri, 1959 (Innes & Nickerson, 1970). In a previous study, intracerebroventricular injection of histamine was shown to induce an antidiuretic response which has been attributed to a massive release of catecholamines (Bhargava et al, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…Intracerebroventricular (i.c.v. ) injections of aconitine were made through a stainless steel cannula introduced into the lateral ventricle according to the method descrilbed by Bhargava & Tangri (1959). Aspiration of cerebrospinal fluid indicated the proper placement of the cannula, which was confirmed at necropsy.…”
Section: Methodsmentioning
confidence: 99%
“…The left common carotid artery was cannulated to record the blood pres sure with a mercury manometer on smoked paper. The drugs were administered in the left lateral cerebral ventricle (intraventricularly) through a polythene cannula implanted according to the technique of Bhargava and Tangri (6). The drugs were administered dissolved in 0.25 ml distilled water (lysergic acid diethylamide tartrate) or normal saline (morphine hydrochloride) followed by same volume of the blank fluid.…”
Section: Methodsmentioning
confidence: 99%